Adverse effects of finasteride in men treated for benign prostatic hyperplasia and androgenetic alopecia - a literature review - Kruk, Adrian; Dorosz, Aleksandra; Skoczeń, Agnieszka; Kulesza, Michał; Wawrzynów, Weronika; Jakubowska, Magdalena Maria; Rutecka, Natalia; Kaczmarek, Błażej; Miłoś Martyna; Kuśnierz-Gibała, Agata (Journal of Education, Health and Sport, 2025)
Background Finasteride, a selective inhibitor of the enzyme 5-alpha reductase type II, is extensively utilized in the management of androgenetic alopecia (AGA) and benign prostatic hyperplasia (BPH). By reducing the conversion of testosterone to dihydrotestosterone (DHT), finasteride effectively mitigates the pathophysiological mechanisms underlying these conditions. Despite its proven efficacy, the therapeutic use of finasteride has been associated with a spectrum of adverse effects, particularly in the domains of sexual, neuropsychiatric, and endocrine health. This review aims to comprehensively analyze the incidence, pathophysiology, and clinical management of adverse effects related to finasteride therapy. Material and methods A comprehensive search of databases, including PubMed and Google Scholar, was conducted using the keywords mentioned below. Conclusions Finasteride is considered a safe and effective medication for the treatment of androgenetic alopecia and benign prostatic hyperplasia, with a well-documented safety profile. However, its use may be associated with adverse effects, including sexual dysfunction and psychological symptoms, which can impact patient satisfaction and adherence to treatment. Although these side effects are typically reversible upon discontinuation, clinicians should discuss potential risks with patients and implement monitoring strategies to ensure optimal outcomes and patient confidence in therapy.